Allogeneic hematopoietic stem cell transplantation with myeloablative conditioning for adult cerebral X‐linked adrenoleukodystrophy. Issue 2 (11th February 2019) - Waldhüter, Nils; Köhler, Wolfgang; Hemmati, Philipp G.; Jehn, Christian; Peceny, Rudolf; Vuong, Giang L.; Arnold, Renate; Kühl, Jörn‐Sven
Abstract: The adult cerebral form of X‐linked adrenoleukodystrophy (ACALD), an acute inflammatory demyelinating disease, results in a rapidly progressive neurodegeneration, typically leading to severe disability or death within a few years after onset. We have treated 15 men who had developed ACALD with allogeneic hematopoietic stem cell transplantation (HSCT) from matched donors after myeloablative conditioning with busulfan and cyclophosphamide. All patients engrafted and 11 survived (estimated survival 73 ± 11%), 8 with stable cognition and 7 of them with stable motor function (estimated event‐free survival 36 ± 17%). Death after transplantation occurred within the first year after HSCT and was caused either primarily by infection ( N = 3) or due to disease progression triggered by infection ( N = 1). Patients with minor myelopathic symptoms ( N = 4) or with no or mild cerebral symptoms pre‐transplant ( N = 7) had an excellent outcome. In contrast, no patient with major neurological symptoms associated with an extensive involvement of pyramidal tract fibres in the internal capsule ( N = 5) survived without cognitive deterioration. Notably, early leukocyte recovery was associated with dismal outcome for yet unknown reasons. All 10 tested survivors showed a reduction of plasma hexacosanoic acid (C26:0) in the absence of Lorenzo's oil. Over time, the event‐free survival could be improved from 2 out of 8 patients (25%) before 2013 to 5 out of 7 patients (71%) thereafter. Therefore, allogeneic HSCT appears to be a suitable treatment option for carefully selected ACALD patients when transplanted from matched donors after myeloablative, busulfan‐based conditioning.